1997
DOI: 10.1007/bf02766144
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing patients’ decision not to repeat IVF

Abstract: Women who did not pursue a second in vitro fertilization cycle after a failed cycle were surveyed. The major reason for not pursuing a second cyclewas financial.KEY WORDS: finance; in vitro fertilization; psychologic stress. ~TRODUCTIONIn vitro fertilization (IVF) is still generally considered to be the last step for couples who are being treated for infertility. There have been many studies regarding the stress of infertility and specifically the stress of IVF. Collins et aL (1) examined the stress associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 7 publications
0
25
0
2
Order By: Relevance
“…These findings suggest that wealthier families joined the registry when compared to the general U.S. population. The well-documented high cost of ART suggests that household income may greatly influence who receives ART (18,19). Given the demographics in our sample, we do not believe that the difference in family income is likely to account for the high rate of BWS after ART.…”
Section: Discussionmentioning
confidence: 91%
“…These findings suggest that wealthier families joined the registry when compared to the general U.S. population. The well-documented high cost of ART suggests that household income may greatly influence who receives ART (18,19). Given the demographics in our sample, we do not believe that the difference in family income is likely to account for the high rate of BWS after ART.…”
Section: Discussionmentioning
confidence: 91%
“…In this analysis, we observed that patients spent an average of 125 hours pursuing treatment. Cost overall is continually cited as a reason why patients choose not to pursue fertility care or discontinue care prior to achieving pregnancy (11, 12), and this is true even in countries where infertility services are subsidized (13, 14), suggesting a significant impact of indirect and time costs. This phenomenon is not unique to fertility care.…”
Section: Discussionmentioning
confidence: 99%
“…If the latter, their continuing treatment would have decreased the overall success rates. Nevertheless, studies have shown that patient dropout may occur for many reasons other than poor prognosis (26,27). One such reason, financial, is less of an issue in a mandated state such as Massachusetts.…”
Section: Discussionmentioning
confidence: 99%